2021
DOI: 10.2166/wh.2021.175
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental surveillance of Legionella pneumophila in hot water systems of hotels in Morocco

Abstract: Objective: Environmental monitoring of Legionella in hot water systems of hotels in Morocco was performed during the period from January 2016 to April 2018. A total of 149 water samples from 118 different hotels were analyzed. Methods: A total of 149 water samples from 118 different hotels were analyzed. Possible risk factors were prospectively recorded, and data were analyzed in connection with building and plumbing systems characteristics. Data about building and risk factors were collected through a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…L. pneumophila was isolated in 23.1% (25/108) of the total samples, with a range from 50 CFU/L to 3000 CFU/L. Previous studies reported widely varying proportions of Legionella -positive samples in hotel and public building hot water systems: 3.1% in a study in Japan [ 18 ], 8.5% in Spain [ 19 ], 18.5% in Greece [ 20 ], 51.7 in Morocco [ 21 ], and 60.5% in Italy [ 22 ]. Table 1 shows that 15 (28.8%) water samples from galvanized iron pipes were positive for L. pneumophila compared with 10 (17.8%) positive samples from plastic pipes, which was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…L. pneumophila was isolated in 23.1% (25/108) of the total samples, with a range from 50 CFU/L to 3000 CFU/L. Previous studies reported widely varying proportions of Legionella -positive samples in hotel and public building hot water systems: 3.1% in a study in Japan [ 18 ], 8.5% in Spain [ 19 ], 18.5% in Greece [ 20 ], 51.7 in Morocco [ 21 ], and 60.5% in Italy [ 22 ]. Table 1 shows that 15 (28.8%) water samples from galvanized iron pipes were positive for L. pneumophila compared with 10 (17.8%) positive samples from plastic pipes, which was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…Legionellosis (Legionnaires’ disease), in fact, is a form of pneumonia interstitial which is normally transmitted via aerosol-containing bacteria, belonging to the genus Legionella that may be present in contaminated water sources, such as domestic hot water, fountains, equipment for respiratory therapy, cooling towers and other devices [ 4 ]. Legionellosis is often associated with travel and with staying in hotels [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%